Differential effects of IL-15 on the generation, maintenance and cytotoxic potential of adaptive cellular responses induced by DNA vaccination. Issue 9 (25th February 2015) - Li, Jinyao; Valentin, Antonio; Ng, Sinnie; Beach, Rachel Kelly; Alicea, Candido; Bergamaschi, Cristina; Felber, Barbara K.; Pavlakis, George N.
Abstract IL-15 is an important cytokine for the regulation of lymphocyte homeostasis. However, the role of IL-15 in the generation, maintenance and cytotoxic potential of antigen specific T cells is not fully understood. Because the route of antigenic delivery and the vaccine modality could influence the IL-15 requirement for mounting and preserving cytotoxic T cell responses, we have investigated the immunogenicity of DNA-based vaccines in IL-15 KO mice. DNA vaccination with SIV Gag induced antigen-specific CD4+ and CD8+ T cells in the absence of IL-15. However, the absolute number of antigen-specific CD8+ T cells was decreased in IL-15 KO mice compared to WT animals, suggesting that IL-15 is important for the generation of maximal number of antigen-specific CD8+ T cells. Interestingly, antigen-specific memory CD8 cells could be efficiently boosted 8 months after the final vaccination in both WT and KO strains of mice, suggesting that the maintenance of antigen-specific long-term memory T cells induced by DNA vaccination is comparable in the absence and presence of IL-15. Importantly, boosting by DNA 8-months after vaccination revealed severely reduced granzyme B content in CD8+ T cells of IL-15 KO mice compared to WT mice. This suggests that the cytotoxic potential of the long-term memory CD8+ T cells is impaired. These results suggest that IL-15 is not essential for the generation and maintenance of adaptive cellular responses upon DNA vaccination, but it is critical for the preservation of maximal numbers and for the activity of cytotoxic CD8+ T cells.